2016
DOI: 10.5114/reum.2016.64902
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psoriatic arthritis and costs generated by treatment of psoriatic arthritis patients in the public health system – the case of Poland

Abstract: ObjectiveThe objective of the study was to analyse the prevalence of psoriatic arthritis (PsA) in Poland and to assess the costs generated by treatment of PsA patients in the system of public healthcare.Material and methodsThe analysis was based on the database of the public payer, the National Health Fund (NFZ). PsA was defined by the diagnostic ICD-10 codes M07 (Enteropathic arthropathies) and L40.5 (Psoriatic arthropathies). The estimate of the costs was based on the reports submitted to the NFZ by health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…It occurs in 5-40% of patients suffering from psoriasis vulgaris. In 2015 PsA incidence was estimated to be at the level of 3.2/10,000 individuals [1]. Present epidemiological studies have not revealed differences in the incidence of PsA in men and women [2].…”
Section: Epidemiologiamentioning
confidence: 63%
See 1 more Smart Citation
“…It occurs in 5-40% of patients suffering from psoriasis vulgaris. In 2015 PsA incidence was estimated to be at the level of 3.2/10,000 individuals [1]. Present epidemiological studies have not revealed differences in the incidence of PsA in men and women [2].…”
Section: Epidemiologiamentioning
confidence: 63%
“…Występuje u 5-40% chorych na łuszczycę zwykłą. W 2015 roku występowanie ŁZS oszacowano na 3,2/10 000 osób [1]. Aktualne badania epidemiologiczne nie wykazały różnic w częstości zachorowań na ŁZS u mężczyzn i kobiet [2], jednak łuszczyca z zajęciem stawów kręgosłupa częściej występuje u mężczyzn, natomiast postać przypominająca reumatoidalne zapalenie stawów (RZS) u kobiet [3].…”
Section: Epidemiologiaunclassified
“…M07.4, M07.5, M07.6) in years 2008–2018 and found that the number of PsA-specific codes was on average 13.18 times higher (range 11.13–16.09) as compared to IBD-specific codes. Therefore, it should be assumed that: (i) the vast majority of patients reported using the M07 code are patients with PsA; (ii) the method used in our previous study [ 11 ] caused a significant underestimation of PsA prevalence; (iii) inclusion of subjects with M07 code should not lead to a significant overestimation of PsA prevalence (vast majority of those subjects do have PsA).…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, our group published a study on the PsA epidemiology in Poland [ 11 ]. The study involved the analysis of National Health Fund (NHF) database and PsA cases were defined by ICD-10 codes M07 and L40.5.…”
Section: Introductionmentioning
confidence: 99%
“…The study used a method of desk research, namely, secondary statistical analysis of data reported to the National Health Fund in 2008-2017. This method has been successfully used previously in the analysis of NHF data for epidemiological purposes [22][23][24][25]. The National Health Fund is a public payer which has a single-payer status for all healthcare services financed from public funds in Poland.…”
Section: Methodsmentioning
confidence: 99%